Rapid Diagnostic Test (RDT) Prototype Validation Test for SARS CoV-2 Antigen in Comparison With RT-PCR Assay - Devi Rahmadhona (Unram Medical Journal, 2022)
Background: The diagnosis of Coronavirus Disease-2019 (COVID-19) is established based on Real-time reverse transcription-polymerase chain reaction (RT-PCR). However, due to the availibity, high cost and length of time of RT-PCR, a reliable alternative is needeed. Rapid Diagnostic Test (RDT) costs cheaper, near-patient use, and if performed and interpreted correctly can be used in areas without RT-PCR or if immediate diagnosis is needed. Objective : To evaluate the quality of RDT SARS CoV-2 prototype compared to RT-PCR. Methods: The patients in this study were patients with RDT antigen and or RT-PCR SARS-CoV-2 examination at Mataram University Hospital who had approved to be research subject. Nasopharyngeal swab sample was used for RDT Antigen SARS-CoV-2 Prototype. Whereas, nasopharyngeal and oropharyngeal swab sampel were used for RT-PCR SARS-CoV-2. The value of sensitivity, specificity and accuray of RDT prototype were assessed based on the RT-PCR result. Results: Total of 124 samples were included in this study. Approximately 39 (31.4%) were positive and 85 (68.5%) were negative. The sensitivity, specificity and accuracy of the SARS CoV-2 RDT prototype were 92.31% (79.13 - 98.38 %, 95% CI), 97.65% (91.76 - 99.71%, 95% CI) and 97.63 % (93.16 - 99.52 %, 95% CI), respectively. There were 5 discrepancies in RDT prototype results compare to the RT-PCR result. Conclusion: The RDT SARS-CoV-2 Antigen prototype showed good sensitivity, specificity and accuracy. Hence, this RDT has the potential to be used for screening or diagnosis, especially in areas with high disease prevalence and low rescorce setting.